2009
DOI: 10.1002/pi.2570
|View full text |Cite
|
Sign up to set email alerts
|

Schiff base‐substituted polyphenol: synthesis, characterisation and non‐isothermal degradation kinetics

Abstract: BACKGROUND: Polymers of phenols and aromatic amines have emerged as new materials in fields such as superconductors, coatings, laminates, photoresists and high‐temperature environments. The stability, kinetics and associated pollution of the thermal decomposition of oligophenols are of interest for the aforementioned fields. RESULTS: A new Schiff base polymer, derived from N,N′‐bis(2‐hydroxy‐3‐methoxyphenylmethylidene)‐2,6‐pyridinediamine, was prepared by oxidative polycondensation. Characterisations using Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…At present, there have been no computational investigations on the catalytic mechanism of saccharopine reductase. However, Schiff base formation has been extensively studied both experimentally and computationally due in part to their common occurrence as reaction intermediates in biochemistry and chemistry [ 4 , 7 , 8 , 9 ]. From these studies it has been shown that Schiff base formation depends on several factors including the solvent, pH, and the chemical nature of the reactants [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there have been no computational investigations on the catalytic mechanism of saccharopine reductase. However, Schiff base formation has been extensively studied both experimentally and computationally due in part to their common occurrence as reaction intermediates in biochemistry and chemistry [ 4 , 7 , 8 , 9 ]. From these studies it has been shown that Schiff base formation depends on several factors including the solvent, pH, and the chemical nature of the reactants [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The integral method proposed by Coats and Redfern was used to calculate the activation energy of thermal decomposition using Eq . : ln(g(α)T2)=ln(AREnormaltβ)EnormaltRT where α is the decomposition fraction, T is the absolute temperature, A is the frequency factor, R is gas constant, Enormalt is the activation energy of thermal decomposition, β is the heating rate, and the expressions of g(α) for the different solid‐state mechanisms are used as the reported articles . From the plots of ln[g(α)/T2] vs. 1000/ T , which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that nonisothermal thermogravimetry (TG) is a powerful tool for characterizing the thermal behavior of polymers. 8,9 Dog an et al…”
Section: Introductionmentioning
confidence: 95%